RETRACTED: In silico 3D structure analysis accelerates the solution of a real viral structure and antibodies docking mechanism - Miki, Motohiro; Katayama, Kazuhiko (Frontiers in Microbiology, 2012)
Norwalk viruse (NoV) is responsible for most outbreaks of nonbacterial gastroenteritis. NoV is genetically diverse and show antigenically variable. Recently, we produced a monoclonal antibody called 5B-18 that reacts broadly with NoV genogroup II (GII). We suspected the 5B-18 binds to a conformational epitope on 3D structure of virion. x-ray crystallography showed us that 5B-18 binds to NoV at the P domain, which protrudes from the core surface of the virion. However, there seems to be no space that would allow the IgG to approach the virion. To solve this problem, we used cryo-electron microscopy to examine NoV GII virus-like particles (VLPs). The P domain rises up higher in NoV GII than in NoV GI, and it seems to form an outer layer around the virion. Finally, using in-silico modeling we found the 5B-18 Fab arms and NoV P region are quite flexible, so that 5B-18 can bind the NoV virion from bottom of P domain. This study demonstrates the shortcomings of studying biological phenomenon by only one technique. Each method has limitations. Multiple methods and modeling in-silico are the keys to solving structural problems.